PENGEMBANGAN MEDIA ULAR TANGGA MATERI PERTUMBUHAN DAN PERKEMBANGAN TANAMAN UNTUK MELATIH KEMAMPUAN LITERASI PADA SISWA KELAS III SEKOLAH DASAR - seftia, ifa; Rosida, Henny; Cacik, Sri (JPB - Jurnal Pendidikan Biologi, 2024)
This research is a development research which aims to develop learning media, namely Snakes and Ladders media on Thematic learning materials. The researcher took Theme 1 Sub-theme 4 Growth and Development Plants on Learning Objects 1 in class III SDN Tenggerkulon. The purpose of the researchers to develop the snakes and ladders media is to find out the validity, practicality, and effectiveness of the snakes and ladders media that was developed. Development is carried out using the ADDIE model which consists of 5 (five) stages, namely analyze, design, develop, implement, and evaluate. The data analysis technique used is validity data analysis, practicality data analysis, and effectiveness data analysis. Based on the validation test, it was found that the developed Snakes and Ladders media has sufficiently valid criteria to be used with the percentage for material experts 77%, media experts 92%, and linguists 63.3%, and product revisions have been carried out so that it can be tested in the field. The percentage results for the teacher's response questionnaire were 93.3% with very practical criteria. In the trial to get a percentage of 89% with practical criteria for use in learning. Based on the results of student tests carried out in the trial, it produced a percentage of 82%. The results of the student test in the tryout were 6 students who scored below the KKM and there were 28 students who scored above the KKM.. These results indicate that snakes and ladders media is effective for use by third grade elementary school students